Characteristics of goals and game at the top championships in futsal - Djordje Cuzovic; Zdravko Šolak (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2018)
As characteristics of the goals scored in the futsal, the following are taken into account: the part of the goal that is successfully hit, the part of the field from which the ball was shot, the time that passed from the beginning to the goal scored and the changes of the result during the match. These qualities have been brought into connection with the qualities of the game taking into account the games in the group stage of the competition and the games in the playoffs. The characteristics of the goals are also linked with the results of the matches in which they were achieved and with the result changes during the match. The research was conducted at a set of matches from the futsal competitions played in 2016, at the European Championship and the World Cup. In these competitions, the bottom half of the goal was hit 330 times (68.6%) and the top one 151 times (31.4%). The right side of the goal was hit 249 times (51.8%) and the left one 232 times (48.2%). From penalty area teams scored 39.1% goals and 54.3% out of it. The proportion of goals that the winning teams scored from outside the penalty area is higher in the group stage than in the playoffs. Especially significant was the goal by which one team comes to the lead of two goals advantage. In European Championship and the World Cup, a team was leading by two or more goals during 34% and 38% of the total time, respectively.   RESUMO  Características dos gols e do jogo no top campeonato em Futsal Como características dos gols marcados no futsal, são levados em conta os seguintes: a parte do gol que é acertada com sucesso, a parte do campo de onde a bola foi chutada, o tempo que passou desde o início até o gol marcado e as mudanças do resultado durante a partida. Estas qualidades foram colocadas em conexão com as qualidades do jogo, tendo em conta os jogos na fase de grupos da competição e os jogos nos playoffs. As características dos gols também estão ligadas aos resultados dos jogos em que foram realizados e com as mudanças de resultado durante a partida. A pesquisa foi realizada em um conjunto de partidas das competições de futsal disputadas em 2016, no Campeonato Europeu e na Copa do Mundo. Nestas competições, a metade inferior do gol foi atingida 330 vezes (68,6%) e a superior 151 vezes (31,4%). O lado direito do gol foi atingido 249 vezes (51,8%) e o esquerdo, 232 vezes (48,2%). Por pênalti as equipes marcaram 39,1% das metas e 54,3% delas. A proporção de gols que as equipes vencedoras marcaram de fora da área de penalidade é maior na fase de grupos do que nos playoffs. Especialmente significativo foi o gol pelo qual uma equipe chega à vantagem de dois gols. No Campeonato Europeu e na Copa do Mundo, uma equipe liderava por dois ou mais gols em 34% e 38% do tempo total, respectivamente.